2016
DOI: 10.1007/s11306-016-1130-6
|View full text |Cite
|
Sign up to set email alerts
|

A metabolomic, geographic, and seasonal analysis of the contribution of pollen-derived adenosine to allergic sensitization

Abstract: Background Studies on ragweed and birch pollen extracts suggested that the adenosine content is an important factor in allergic sensitization. However, exposure levels from other pollens and considerations of geographic and seasonal factors have not been evaluated. Objective This study compared the metabolite profile of pollen species important for allergic disease, specifically measured the adenosine content, and evaluated exposure to pollen-derived adenosine. Methods An NMR metabolomics approach was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Bioaccessibility requires knowledge of the kinetic of release of the biochemical constituents of PG but also of their ability to diffuse into the mucus (Mueller et al, 2016). Such information on bioaccessibility remains scarce for PPPG constituents in particular and for allergenic pollens in general.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bioaccessibility requires knowledge of the kinetic of release of the biochemical constituents of PG but also of their ability to diffuse into the mucus (Mueller et al, 2016). Such information on bioaccessibility remains scarce for PPPG constituents in particular and for allergenic pollens in general.…”
Section: Discussionmentioning
confidence: 99%
“…Besides bioavailability, bioactivity requires that compounds extracted from PPPGs reach high enough concentrations for activities in physiological conditions. Mueller et al (2016) have for example calculated concentrations of adenosine in nasal conditions based on assumptions on airborne pollen concentrations and of amount of nasal fluid. They conclude that, most of the time, nasal level of adenosine brought by PGs are too low to reach physiological levels (Mueller et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter also instructed activated epithelial cells to secrete IL-8, similarly to the complete pollen extract [138]. However, the significance of adenosine in allergic sensitization has been questioned by Mueller et al who quantified adenosine levels in various pollen extracts and concluded that the measured amounts too low to exert a physiological effect [139]. The discrepancy of these results might be explained by environmental factors influencing the adenosine content in pollen.…”
Section: Other Contributing Factorsmentioning
confidence: 99%